On-Center/Inhibitory-Surround Decorrelation via Intraglomerular Inhibition in the Olfactory Bulb Glomerular Layer - Cleland, Thomas A.; Linster, Christiane (Frontiers in Integrative Neuroscience, 2012)
Classical lateral inhibition, which relies on spatially-ordered neural representations of physical stimuli, cannot decorrelate sensory representations in which stimulus properties are represented non-topographically. Recent theoretical and experimental studies indicate that such a non-topographical representation of olfactory stimuli predominates in olfactory bulb, thereby refuting the classical view that olfactory decorrelation is mediated by lateral inhibition comparable to that in the retina. Questions persist, however, regarding how well non-topographical decorrelation models can replicate the inhibitory “surround” that has been observed experimentally (with respect to odor feature-similarity) in olfactory bulb principal neurons, analogous to the spatial inhibitory surround generated by lateral inhibition in retina. Using two contrasting scenarios of stimulus representation – one “retinotopically” organized and one in which receptive fields are unpredictably distributed as they are in olfactory bulb – we here show that intracolumnar inhibitory interactions between local interneurons and principal neurons successfully decorrelate similar sensory representations irrespective of the scenario of representation. In contrast, lateral inhibitory interactions between these same neurons in neighboring columns are only able to effectively decorrelate topographically organized representations. While anatomical substrates superficially consistent with both types of inhibition exist in olfactory bulb, of the two only local intraglomerular inhibition suffices to mediate olfactory decorrelation.